von Willebrand Factor and Platelet Glycoprotein Ib: A Thromboinflammatory Axis in Stroke - Denorme, Frederik; Vanhoorelbeke, Karen; De Meyer, Simon F. (Frontiers in Immunology, 2019)
von Willebrand factor (VWF) and platelets are key mediators of normal hemostasis. At sites of vascular injury, VWF recruits platelets via binding to the platelet receptor glycoprotein Ibα (GPIbα). Over the past decades, it has become clear that many hemostatic factors, including VWF and platelets, are also involved in inflammatory processes, forming intriguing links between hemostasis, thrombosis, and inflammation. The so-called “thrombo-inflammatory” nature of the VWF-platelet axis becomes increasingly recognized in different cardiovascular pathologies, making it a potential therapeutic target to interfere with both thrombosis and inflammation. In this review, we discuss the current evidence for the thrombo-inflammatory activity of VWF with a focus on the VWF-GPIbα axis and discuss its implications in the setting of ischemic stroke.